Pengaruh Lingkungan Kerja Non Fisik Dan Disiplin Kerja Terhadap Kinerja Karyawan Rawat Jalan Di Rumah Sakit Siloam Tb Simatupang - Faizah Faizah; Angga Juanda (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the partial and simultaneous influence between the non-physical work environment and work discipline on employee performance in Outpatients at Siloam Hospital TB Simatupang . The method used in this study is quantitative with a descriptive associative approach and saturated sampling technique with a population and sample of 87 respondents. The value of the correlation coefficient of the non-physical work environment and work discipline on employee performance is at the level of 0.936, so the level of correlation between variables is interpreted as very strong. Hypothesis test obtained X values of 1 t count t table or ( 3.646 > ttable 1.988 ) and the value (sig) 0.000 < 0.05 thus shows that there is a positive and significant partial influence between the non-physical work environment on employee performance in Outpatient Care at Siloam Hospital TB Simatupang . Hypothesis testing obtained X2 values . t count > t table or ( 5.914 ttable 1.988 ) and the value (sig) 0.000 < 0.05 thus shows that there is a positive and significant partial influence between work discipline on employee performance in Outpatient Care at Siloam Hospital Tb Simatupang . The results of this study are non-physical work environment (X 1 ) and work discipline (X 2 ) with multiple regression equation Y = 0.156 + 0.457X 1 + 0.743X 2 . which can be interpreted as non-physical work environment and work discipline have a positive effect on employee performance . Partial or simultaneous hypothesis testing obtained f count f table ( 296,398 > 3.11 ) and significant < 0.05 (0.000 < 0.05) then Ho3 is rejected and Ha3 is accepted, meaning the non-physical work environment (X 1 ) and work discipline (X 2 ) have a positive and significant effect on employee performance . The results of the analysis of the Determination coefficient tested together have an influence of 0.876 or 87.6% while the remaining 12.4% is influenced by other factors.